(untitled) (Bangladesh Journal of Medical Science, 2012)
After the concept of evidence based medicine it became important all over the world to have more structured, clinical oriented curriculum. According to the United Nations, Asia is divided into five sub regions. Brunei, Cambodia, East Timor, Indonesia, Laos, Malaysia, Myanmar, Philippines, Singapore, Thailand, and Vietnam belong to South-eastern Asia. To cope with the rapid changes in medical education curriculum most of the medical school in Asia particularly south East Asian countries adopted took up curriculum to fit to the current need. Medical education in Malaysia and Singapore developed similarly as the two countries together formed a federation in the British Empire until independence in 1957. Currently, in medical education, a trend has emerged to utilize "trustable research findings" in place of "personal opinions" as a basis for educational management and decision-making. Several of Malaysia’s medical schools partner with other European, American and Asian schools, and students sometimes earn the certification or accreditation to practice in those countries as well. In the context of changing medical education system, South East Asia is also adopting up to date medical curriculum for the medical students in these countries. As a result rapid changes in curriculum with special focus on research these schools likely to become a hub of ’educational tourist’. Keywords: Medical education; Malaysia; South East Asia. DOI: http://dx.doi.org/10.3329/bjms.v10i4.9491 BJMS 2011; 10 (4): 226-229